ANALYSIS OF FACTORS AFFECTING OHSD IN MINING SECTOR MANUFACTURING COMPANIES LISTED ON THE IDX - Amaliyah, Desy; Nurhadiyati, Siti (Ridwan Institute, 2024)
Occupational Health and Safety (K3) is part of corporate social responsibility. K3 is our effort to create a healthy and safe work environment, so as to reduce the probability of work accidents/illnesses due to negligence which results in demotivation and deficiencies in work productivity. The research method used was a descriptive quantitative research method using descriptive statistical data, with sample selection using purposive sampling. The data used is secondary data from annual financial reports. The data were taken from annual reports, sustainability reports, and financial reports obtained from relevant sources. The research used multiple regression analysis methods with the help of the SPSS Version 26 program. The results show that size influences OHSD disclosures, Leverage does not influence OHSD disclosures, Profitability does not influence OHSD disclosures, Board of Commissioners size does not. influence on OHSD disclosure, shareholder size influences OHSD disclosure. So this research can be used to look at the factors that influence the disclosure of OHSD.